The Use of Conversational Implicature and Speech Acts in Tema Indonesia Youtube Channels - Mulyani, Ani; Mubarok, Yasir; Nurhuda , Zamzam (Journal of Languages and Language Teaching, 2025)
This study aims to describe the use of conversational implicature and types of speech acts in informal conversations in five episodes of the Tema Indonesia YouTube channel, namely DPN, Comedy Buddy, Gegerrr, Sekolah Ngawur, and Pods Tema. This study uses a qualitative descriptive approach with an interactive model data analysis technique from Miles and Huberman (1994). The theories used are Searle's Speech Acts Theory (1969) and Grice's Conversational Implicature Theory (1975). The results of the study showed that 30 conversational implicature data were found, consisting of 53% particularized conversational implicature and 47% generalized conversational implicature. Most of the utterances are expressive speech acts that function to convey social criticism, emotional evaluation, and light satire. In addition, representative and directive speech acts were also found, although with a lower frequency, functioning to provide information and suggestions in a subtle manner. No commissive or declarative speech acts were found in the data. These findings suggest that communication in Tema Indonesia is reflective, critical, and entertaining, relying on humor and implicature to strengthen the audience's emotional engagement and encourage active interpretation of implied meanings. This research confirms that digital communication not only forms entertainment, but also a space for social and political discussion packaged in a light-hearted style.